2000
DOI: 10.1046/j.1365-313x.2000.00782.x
|View full text |Cite
|
Sign up to set email alerts
|

FLP‐mediated recombination for use in hybrid plant production

Abstract: SummaryWe have studied the feasibility in Arabidopsis of using a site-speci®c recombination system FLP/FRT, from the 2 mm plasmid of yeast, for making plant hybrids. Initially, Arabidopsis plants expressing the FLP sitespeci®c recombinase were crossed with plants transformed with a vector containing kanamycinresistance gene (npt)¯anked by FRT sites, which also served to separate the CaMV35S promoter from a promoterless gusA. Hybrid progeny were tested for excision of the npt gene and the positioning of 35S pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
39
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(42 citation statements)
references
References 49 publications
3
39
0
Order By: Relevance
“…In addition, for efficient integration, the minimal sizes of attB and attP are 36 bp and 48 bp, respectively. This site-specific recombination system is efficient and simple to use; thus, it could have applications for the manipulation of DNA in vitro.Site-specific recombinases have been widely used in genetic engineering: for example, in vitro cloning, plant and mammalian cell genome modification, and gene therapy (3,11,12,15,16). Nearly all site-specific recombinases can be classified as tyrosine recombinases, also known as the integrase family, or serine recombinases, also known as the resolvase/invertase family, based on comparisons of amino acid sequences and different mechanisms of catalysis; these two types use tyrosine or serine, respectively, to attack the DNA sugar-phosphate backbone (14,18,20).…”
mentioning
confidence: 99%
“…In addition, for efficient integration, the minimal sizes of attB and attP are 36 bp and 48 bp, respectively. This site-specific recombination system is efficient and simple to use; thus, it could have applications for the manipulation of DNA in vitro.Site-specific recombinases have been widely used in genetic engineering: for example, in vitro cloning, plant and mammalian cell genome modification, and gene therapy (3,11,12,15,16). Nearly all site-specific recombinases can be classified as tyrosine recombinases, also known as the integrase family, or serine recombinases, also known as the resolvase/invertase family, based on comparisons of amino acid sequences and different mechanisms of catalysis; these two types use tyrosine or serine, respectively, to attack the DNA sugar-phosphate backbone (14,18,20).…”
mentioning
confidence: 99%
“…CMS has been observed in over 150 plant species including maize, rice, and wheat [70,71]. Detasseling (for maize) or emasculation procedures and/or CMS systems are lacking or deficient in many important crops still grown as inbred or partially domesticated varieties [36,72,73]. Given the accumulated knowledge of CMS systems and the desirability of developing male sterility systems lacking the shortcomings of most CMS systems, a number of strategies for engineering male sterility have been developed to generate male-sterile plants as breeding materials and for gene confinement strategies [2,73,74].…”
Section: Discussionmentioning
confidence: 99%
“…So far we have only shown recombination reactions in the cis configuration, such reactions can be useful to eliminate undesired genes, such as genes for antibiotic resistance or genes that cause male sterility, as is already practiced by using the Cre-lox and FLP-frt systems (Luo et al, 2000;Hoa et al, 2002;Ow, 2002;Puchta, 2003). For the insertion or replacement of genes it still needs to be shown that the Int-catalyzed reactions take place also in the trans configuration (each att site on a different DNA molecule).…”
Section: Discussionmentioning
confidence: 99%